Pain-free grip strength in individuals with lateral elbow tendinopathy: Between- and within-session reliability of one versus three trials. - Hill, Caitlin E.; Heales, Luke J.; Stanton, Robert; Kean, Crystal O. (Physiotherapy Theory & Practice, 2023)
Pain-free grip strength is an important outcome measure in lateral elbow tendinopathy (LET); yet, the reliability and minimum detectable change (MDC) in functional positions are unknown. The purpose of this study is to examine the between- and within-session pain-free grip strength reliability and MDC in LET. Twenty-three individuals with LET completed three pain-free grip strength trials with the elbow flexed and extended. The first trial and the mean of three trials were analyzed. Between-session data were collected 2–28 days apart. Within-session data were collected 20–30 min apart. Between-session intraclass correlation coefficients (ICCs) were good (ICC2,1 = 0.75) for single trials (flexed), excellent (ICC2,1 = 0.89–0.94) for single trials (extended), and excellent for the mean of three trials (both positions). Within-session ICCs were excellent for single (ICC2,1 = 0.89–0.91) and the mean of three trials (ICC2,3 = 0.96–0.98) in both positions. Between-session flexed MDCs were 133 N (single) versus 90 N (mean) and extended MDCs were 118 N (single) versus 92 N (mean). Within-session flexed MDCs were 79 N (single) versus 52 N (mean) and extended MDCs were 125 N (single) versus 46 N (mean). Using the mean of three trials is recommended, and clinicians can be confident of true change if between-session differences are >92 N and within-session differences are >52 N.